Perlindungan Hukum terhadap Konsumen Akibat Cacat Produk pada Saat Produksi Ditinjau dari Undang – Undang No. 8 Tahun 1999 - I Nyoman Kerthia Wahyudi; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Fakultas Hukum, Universitas Warmadewa, 2022)
Lack of supervision and accuracy from the authorized body causes the circulation of defective products to the market. Defective products are products that are not fit for consumption and do not provide safety requirements for consumers. To meet market demand for high-quality products, products are often not looked after properly, as a result, defective products are often encountered. Consumers often do not get full responsibility from businesses regarding traded defective products. Thus, this study aims to discuss legal remedies that can be taken by consumers against defective products and analyze the responsibility of producers as business actors against defective products that harm consumers. Using a normative legal research method with a law approach. Primary and secondary sources of law. Legal materials are collected using an inventory technique with the relevant search and then classified, recorded, cited and summarized. The results of the study indicate that the losses suffered by consumers require consumers to take legal action to guarantee their rights. Legal efforts can be taken through consumer dispute resolution efforts in litigation and non-litigation. Business actors who produce/trade defective products may be subject to UUPK sanctions in the form of civil, criminal and administrative sanctions